Destino México : un estudio de las migraciones asiáticas a México, Siglos XIX y XX - Rodríguez Chávez, Javier; Camposortega Cruz, Sergio; González Navarro, Moises; Ota Mishima, María Elena (Book collections on Project MUSE., 1997)
"Contains 10 essays on Asian immigrants who came to Mexico mostly in 20th century. Includes studies of Japanese, Koreans, Arabs, Palestinians, Filipinos, and even Sikhs from India. Rosario Cardiel Marín's essay on the Chinese in Baja California also is of interest. Provides a different picture for a country usually thought of as extremely homogeneous"--Handbook of Latin American Studies, v. 58.